Un réformateur et la science - Salam Kawakibi (Revue des Mondes Musulmans et de la Méditerranée)
'Abd al-Rahman al-Kawâkibî is one of the Syrian intellectuals who, at the end of the 19th century, took refuge in Egypt with a view to escaping from Ottoman Sultan's authoritarianism. Through many articles and books, he developed a political line of thought in reference to the relationship between power and religion. His thinking argues that the cause of the decline of Muslim countries lies in the deprivation of their “rights of reason”. In his view, the submission to a despotic government and the development of modern sciences are not at all compatible with each other; the latter are generally viewed as a threat by despots for whom ignorance is the best option. Consequently, in Kawakibi's mind, the dissemination of knowledge among people is the only way which leads to freedom as well as to the emancipation of mankind as opposed to an illegitimate power which distorts religion to serve its own interests.